A educação matemática e o cuidado de si: possibilidades foucaultianas - Silva, Michela Tuchapesk da [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In line with the Philosophy of Difference, this research puts into practice the transverse movements contrary to the vertical and horizontal movements in school with the goal of presenting discussions about the possibilities of mathematics teachers in regard to the 'autonomy', the 'self-care' according to Michel Foucault (2005, 2006, 2007, 2010). For this, we made use of the method of cartography - related to the human subjectivity - investigating the practices and techniques of subjectivism of the self in accordance with the ethics of Foucault's individual. Thus, in a public school in Sao Paulo state countryside we held theoretical and practical workshops with a group of nine math teachers, aiming at the possibility of creating new ways of existence, new subjectivity, moving concepts and other thoughts such as: what are the possibilities of being a teacher? Do mathematics teachers take autonomous decisions, i.e., taken by themselves? Or do they work on the common sense as automatic pilots? Do teachers have control of their school practices and tactics? Or are the teachers controlled by the mainstream power and knowledge? Will the power always manipulate us? Is there resistance in schools? Or we can trace other pathways in education; pathways to permanent resistance and discussion? Therefore, these workshops were strong enough to establish a new territory in education. Contrary to a vertical or horizontal territory, the power of transverse movement produced almost rhisomatically escape routes, new ways of existing, different perspectives and some other thoughts

Essa pesquisa, em consonância com a Filosofia da Diferença, coloca em prática movimentos transversais contrários aos movimentos verticais e horizontais na escola. O objetivo é apresentar discussões acerca das possibilidades do professor de Matemática no que se refere a 'autonomia' e o 'cuidado de si' segundo Michel Foucault (2005, 2006, 2007, 2010). Para isso, nos apropriamos do método da cartografia - relacionada à subjetividade humana - investigando as práticas e técnicas de subjetivação do eu segundo a ética do sujeito foucaultiano. Assim, numa escola pública no interior do Estado de São Paulo proporcionamos encontros, de teoria e prática, com nove professores de Matemática, visando a possibilidade de constituir novos modos de existência, novas subjetividades, movimentando conceitos e pensamentos outros como: Quais as possibilidades de ser professor? Os professores de Matemática tomam decisões autônomas, ou seja, decididas por ele? Ou trabalham no piloto automático do senso comum? Os professores têm controle das suas práticas e táticas escolares? Ou são controlados pelos poderes e saberes vigentes? Há resistências nas escolas? Sempre seremos manipulados pelo poder? Ou podemos traçar caminhos outros na educação, caminhos para resistência e lutas permanentes. Portanto, esses encontros foram suficientemente fortes para estabelecer um novo território em educação. Contrário a um território verticalizado ou horizontalizado a potência do movimento transversal produziu quase que rizomaticamente rotas de fuga, novos modos de existir, novos olhares e pensamentos outros
Keywords: Foucault, Michel, 1926-1984; Mathematics - Study and teaching; Matemática - Estudo e ensino; Professores de matematica; Cartografia; Autonomia (Psicologia); Subjetividade